Nutritional study of jelawat, Leptobarbus hoevenii (Bleeker), fed on pelleted feed - Law, A.T. (Elsevier Science, 1984)
The digestion coefficients of the nutrients in the ingredients used in formulating the diet (MARDI-37%) for the culturing of jelawat were evaluated. Cr2O3 was used as an internal marker for the evaluation of digestibility. The results indicate that jelawat can digest 100% of the protein, fat, carbohydrate and gross energy in fish meal, but only 69.50% protein, 60.70% fat, 73.82% carbohydrate and 59.30% gross energy in soyabean meal. Surprisingly, this fish can digest copra cake meal, an agricultural by-product in Malaysia, better than soyabean meal; the values were 75.36% protein, 98.36% fat, 50.03% carbohydrate, and 73.21% gross energy. Digestibility of maize, rice bran and tapioca was poor in this fish. There were no significant differences in the digestibility of dry matter, protein, fat, carbohydrate, ash and gross energy of the reference diet in jelawat specimens whose total length was greater than 12 cm, whereas in fish smaller than 12 cm digestibility was significantly lower.